Bridging the Gaps in Girls’ Education The Case of Kasturba Gandhi Balika Vidyalayas (KGBVs) - Anand, Sarita; Das, Bidisha (JOURNAL OF INDIAN EDUCATION, 2017)
Education for girls has been a high priority for the Government of India. With the aim of targeting the pockets where girls’ education is lagging, the Government of India launched Kasturba Gandhi Balika Vidyalaya (KGBV) scheme in 2004 for setting up residential schools at upper primary level for girls belonging to the SC, ST, OBC and minorities in difficult areas. The study aims at understanding the motivations and perceptions of young girls studying in selected KGBVs. The major stakeholders of the scheme are the teachers and wardens of the KGBVs, parents of girls studying in KGBVs, and the local NGO officials were also interviewed to gain a holistic perspective about the KGBVs.